Design of Broadband Dual-Frequency Microstrip Patch Antenna with Modified Sierpinski Fractal Geometry - Ngu, Sze Song; Kho, Lee Chin; Bong, David B L; Martin, Anyi (IEEE, 2007)
Fractal antennas have the characteristic of radiating in multiple frequencies through the property of self similarity that fractal shapes possess. By connecting fractal shaped antennas, wideband coverage can be achieved. Microstrip patch antennas with Sierpinski fractal geometry can be tuned, by design, to work exactly at the bands of interest, through judicious choice of the fractal designs and iteration. Therefore, a broadband dual-frequency microstrip patch antenna with modified Sierpienski fractal geometry is designed by using Microwave Office 2002 simulation software. The broadband and multiple frequency characteristics of fractal antennas will be demonstrated. The performance of microstrip patch antenna with the classic and modified Sierpinski fractal geometries will be presented